ANALISIS KANDUNGAN PEMANIS BUATAN SIKLAMAT PADA SIRUP YANG BEREDAR DIPASAR BESAR MALANG SECARA KUANTITATIF MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Jayadi, Lukky; Hernaningsih, Maritha (Jurnal Riset Kefarmasian Indonesia, 2021)
Sweeteners are chemical compounds that are often added and used for industrial food processing products as well as beverages and foods, sweeteners consist of natural sweeteners and synthetic sweeteners, one of the synthetic sweeteners is sodium cyclamate. This study aims to identify and determine the level of sodium cyclamate in syrup by UV spectrophotometry method and to determine the level of sodium cyclamate in syrup is still safe for consumption. The type of research is experimental and descriptive. The research sample used is syrup which is sold in the big market of Malang City. The method used for the determination of sodium cyclamate levels was done by UV spectrophotometry whose absorption was measured at a maximum wavelength of 314 nm. The results of the quantitative analysis showed that there were positive samples containing sodium cyclamate, namely sample 1, sample 2 and sample 3. The assay results in sample 1 were 238.78 mg/kg, sample 2 was 239.65 mg/kg and sample 3 was 241.39 mg/kg. Of the three samples tested for levels of cyclamate in syrup sold in the big market in Malang City, they still meet the requirements set by the head of the Food and Drug Supervisory Agency.